Laparoscopic management of rare “ H type” duplication of gall bladder - Dr. Anurag Mishra; Dr. Md Abu Masud Ansari; Dr. Shivanshu Misra (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
A duplicated gallbladder is a rare congenital anomaly with an incidence of 1:4000 live births. They can remain asymptomatic and identified incidentally or present as acute cholecystitis, empyema, torsion, cholecystoenteric fistula, Gall bladder lump, or carcinoma. Here the current case is about discussing a case of a 25-year-old female who presented with symptomatic gallstone disease with a duplicated gallbladder having multiple stones in both the gallbladders. MRCP performed preoperatively revealed Y type duplication (double Gall bladder with common cystic duct). Laparoscopic cholecystectomy was performed and it finally revealed H type duplication (double Gall bladder with separate cystic ducts for each Gall Bladder).